2021
DOI: 10.3390/ijerph182212240
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Graded Motor Imagery Intervention for Phantom Limb Pain in Patients with Amputations (GraMI Protocol): A Delphi Study

Abstract: Background: Phantom limb pain can be defined as discomfort or pain in a missing part of the limb. The aims of this study were to develop and validate, through a Delphi methodology, a graded motor imagery protocol in order to reduce phantom limb pain. Method: Physiotherapists and/or occupational therapists with experience in research and a minimum clinical experience of five years in the field of neurorehabilitation and/or pain were recruited by part of a group of experts to assess the intervention. The study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In addition, they are more intensive and long-lasting techniques that further promote neuroplasticity and brain changes. 13,16,17,40 In this line, Limakatso et al, using the Delphi methodology, showed high concordance of a panel of experts recognizing GMI for the conventional treatment of PLP. 41…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, they are more intensive and long-lasting techniques that further promote neuroplasticity and brain changes. 13,16,17,40 In this line, Limakatso et al, using the Delphi methodology, showed high concordance of a panel of experts recognizing GMI for the conventional treatment of PLP. 41…”
Section: Discussionmentioning
confidence: 92%
“…In addition, they are more intensive and long-lasting techniques that further promote neuroplasticity and brain changes. 13,16,17,40 In this line, Limakatso et al, using the Delphi methodology, showed high concordance of a panel of experts recognizing GMI for the conventional treatment of PLP. 41 Consequently, the type of intervention, frequency, and duration might be a differential factor in the improvement of PLP in patients who have suffered an amputation.…”
Section: Authorsmentioning
confidence: 93%
“…Twenty studies were excluded because they did not meet the eligibility criteria. These studies included discrepancies or deficiencies in the order of the stages of GMI [18,[31][32][33][34][35], lack of full-text access [36][37][38][39], protocol of the study [40,41], not fully implementing the GMI [42,43], study type (1 letter to the editor, 2 abstract conference papers, 2 reviews) [5,[44][45][46][47] and were excluded due to unclear outcome parameters [13]. As a result, 17 eligible studies were reviewed, and after reviewing the reference sections of these studies, one more study [6] was added, and a total of 18 articles were included in this systematic review (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Intervention in the experimental group. The participants from the experimental group will perform the GraMI protocol [26]. This consists of three consecutive and progressive techniques: laterality recognition, motor imagery and mirror therapy.…”
Section: Stage 2: Ecamentioning
confidence: 99%
“…As a result, a systematic review has been conducted prior to this study to determine the effectiveness of GMI and its components on PLP in the amputee patient. Through this review, it was possible to define a protocol that has been validated by a group of experts in the field of neurorehabilitation and/or pain via a study using Delphi methodology [ 26 ], which has resulted in the GMI-based GraMI protocol.…”
Section: Introductionmentioning
confidence: 99%